2018
DOI: 10.1039/c7nj04707j
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and exploiting different catalytic systems for the direct conversion of cellulose into levulinic acid

Abstract: The single step conversion of cellulose into levulinic acid has been studied under hydrothermal conditions with several catalytic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Ionic liquids (ILs) are organic salts composed of an organic cation and an organic or an inorganic anion which are liquid below 100 C. The physico-chemical properties of these neoteric solvents (e.g., negligible vapor pressure, wide electrochemical window, high thermal stability, low ammability) [1][2][3] and the possibility to tweak them by changing the constituent ions 4 allowed their use in different elds. ILs have been studied and exploited for instance in the dissolution, fractionation and functionalization of biomasses, [5][6][7][8] in organic synthesis, 9,10 in analytical chemistry, 11 in electrochemistry 12,13 and, more recently, in biological and pharmaceutical applications. 14 Dicationic ionic liquids (DILs) are a subclass of ILs which are characterized by two cationic head groups linked to one another by means of a spacer.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) are organic salts composed of an organic cation and an organic or an inorganic anion which are liquid below 100 C. The physico-chemical properties of these neoteric solvents (e.g., negligible vapor pressure, wide electrochemical window, high thermal stability, low ammability) [1][2][3] and the possibility to tweak them by changing the constituent ions 4 allowed their use in different elds. ILs have been studied and exploited for instance in the dissolution, fractionation and functionalization of biomasses, [5][6][7][8] in organic synthesis, 9,10 in analytical chemistry, 11 in electrochemistry 12,13 and, more recently, in biological and pharmaceutical applications. 14 Dicationic ionic liquids (DILs) are a subclass of ILs which are characterized by two cationic head groups linked to one another by means of a spacer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of us reported a novel procedure for the separation of sporopollenin from the other pollen components, using ionic liquids (ILs) 13 . ILs are organic salts which are liquid below 100 °C and, thanks to the possibility to tailor their physico-chemical properties by changing the constituting ion, found use in a wide range of different applications during the last two decades [14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…Shen and coworkers reported that a high catalytic activity for the conversion of cellulose to LA with a yield of 39.4% was achieved in the presence of IL 1-(4-sulfonic acid) butyl-3-methylimidazolium hydrogen sulfate ([BSMim]HSO 4 ) with addition of water at 120°C for 120 min ( [351]. The excellent performance of 0.375 wt% TiOSO 4 was mainly due to the mixed Brønsted-Lewis acid catalytic system.…”
Section: Levulinic Acid (La)mentioning
confidence: 99%